Synthesis and cytotoxicity assay using Brine Shrimp Lethality Test of Cinchonidine Isobutyrate Ester - Mario Mario; Puspa Dewi Lotulung; Gian Primahana; Sylvia Rizky Prima; Muhammad Hanafi (Research Center for Chemistry - LIPI, 2017)
This research was aimed to synthesize cinchonidine isobutyrate ester and conduct a preliminary assay for anticancer agent using cytotoxicity assay to Artemia salina Leach larva, or also known as brine shrimp lethality test (BSLT). Cinchonidine, a compound that has quinoline rings and quiniclidine ring, is a quinine analogue and stereoisomer of cinchonine. Cinchonidine is predicted to have anticancer activity. Synthesized ester was aimed to gain higher lipophilicity. Higher lipophilicity makes it easier for the compund to pass through cell membrane. The esterification process used DMAP as a catalyst, DCC as an activator, and isobutyric acid as a carboxilyc acid. Isobutyric acid is a type of short chained fatty acid that usually acts as an anticancer prodrugs. The product is identified by ESI-MS, FT-IR, 1H-NMR, dan 13C-NMR. Ester cinchonidine isobutyrate is gelatinous and colourless with yield of 21,77%. BSLT result showed that cinchonidine isobutyrate ester had LC50 value of 75.16 ppm which was more toxic than cinchonidine that had LC50 value of 99.2 ppm. It was proved that higher lipophilicity could increase pharmacology activity